Deserción Universitaria en estudiantes de noveno y décimo ciclo de la Carrera de Medicina de la Universidad Nacional de Loja - Ávila Samaniego, Valerie Salomé (2024)
Student dropout is understood as the abandonment of education by students, caused by the combination of multiple factors, thus generating a social problem, a situation that affects many higher education institutions; For this reason, the following research was proposed with the objective of determining the predisposing factors for university dropout in ninth and tenth cycle students of the Faculty of Human Health Medicine, for which a descriptive, crosssectional study was developed, with a sample of 100 students to whom a University student dropout Survey and a Academy Experiences questionnaire – reduce version (QVA-r) was applied. The results showed that 85% of the students were aged 21-25 years; 98% were of mixed race; 69% were women; 97% were single; 4% had children; 7% worked; 28% lived alone and 4% lived with their partner; 27% suffered from illnesses that required continuous medication; the majority came from provinces belonging to zone 7. Socio-economic factors due to low income, factors related to the student's personality such as anxiety, low selfesteem, adaptation problems, cultural factors related to the economic, labour and violent situation of the country, academic factors related to the relationship between teacher-studentadministrative staff were identified as causes of desertion. For these reasons, the university must strengthen the services provided by the University welfare Department to ensure that the student's educational process is not halted due to lack of financial resources or mental health situations